(untitled) (INNOVATIVE ECONOMY, 2023)
Valihura V.A. FISCAL ASYMMETRIES OF THE UKRAINIAN ECONOMY IN THE CONTEXT OF ANTI-CRISIS TAX REGULATION Purpose. The aim of the article is the formulation of proposals for improving taxation of certain branches of the Ukrainian economy in the conditions of martial law and in the process of post-war recovery based on the identification of asymmetries in the tax burden by types of economic activity. Methodology of research. The following general scientific and special methods were used in the research process: analysis, synthesis, induction and deduction - when studying the structure of GDP and tax burden by types of economic activity in Ukraine; description, abstract and logical - when characterizing the directions of reforming the tax system, given in the post-war reconstruction plans of Ukraine; abstraction, description, comparison - to substantiate directions for improvement of taxation of individual branches of the economy of Ukraine. Findings. It was established that the specific weight of certain types of economic activity in the structure of GDP does not always correlate with the share of these types in the structure of tax revenues. This is due to the differentiation of the level of taxation of certain types of economic activity in Ukraine. It is substantiated that, despite large asymmetries in the taxation of certain sectors of the economy in Ukraine, it is impractical to equalize the level of taxation for certain types of activities or sectors of the economy. In the conditions of prolonged martial law and for the period of post-war recovery, it is suggested that in the process of reforming the tax system, the sectoral specifics of Ukraine’s economy, the state of functioning of individual industries and the priority of their products should be taken into account. Originality. The directions for improving the taxation of certain industries and types of activity in Ukraine, given in the post-war recovery plans, are supplemented by proposals regarding the taxation of economic entities in the agricultural and construction sectors of the economy and the sphere of wholesale and retail trade. Practical value. The results of the presented research can be used in the process of improving the tax policy of Ukraine in the conditions of martial law and post-war recovery. Key words: taxation of types of economic activity, level of taxation, taxation of agriculture, taxation of construction.